Revealing Higher Education Students’ Readiness for Abrupt Online Learning in Indonesia amidst Covid-19 (NOBEL: Journal of Literature and Language Teaching, 2021)
COVID 19 pandemic has influenced many sectors, including education. The outbreak hinders teaching and learning activities, which have usually been carried out in a face-to-face meeting. In Higher Education, online learning becomes a crucial need to keep the teaching and learning going on. It has been a sudden shift for students of the English Education Study Program at Tidar University to have online teaching and learning throughout the whole semester. This study explores the students’ readiness for online learning and investigates the aspect that tangles their online learning. A total of 188 students, from first-year students to senior students, participated in this study. The Online Learning Readiness Scale (OLRS) and interview were used to appraise the students’ readiness for online learning. Internet self-efficacy, self-directed learning, learner control, motivation for learning, and online communication self-efficacy were assessed. The result of the scale revealed that the students were at a moderate level of online learning readiness. The highest contribution to their readiness was from their motivation for online learning. Moreover, surprisingly, the biggest challenge was the learner control. They were mainly distracted by other online activities during their online learning. Also, conducting online learning needs to involve various technologies and more structured activities to enhance their readiness.